The influence of helmet on the prevention of maxillofacial fractures sustained during motorcycle accidents. Issue 1 (1st January 2018) - Ruslin, Muhammad; Wolff, Jan; Yusuf, Harmas Yazid; Arifin, Muhammad Zafrullah; Boffano, Paolo; Forouzanfar, Tymour
Abstract: The aim of this study was to assess the effect of half-coverage helmet use in motorcycle accidents and to investigate the difference in neuron-specific enolase serum levels in helmeted and unhelmeted person who had sustained maxillofacial fractures during motorcycle accidents. A total of 48 subjects (22 helmeted and 26 unhelmeted) sustained maxillofacial fractures were divided into three parts: upper, middle, and lower facial. All patients were scored using the Glasgow Coma Scale upon arrival at the hospital. The most prevalent maxillofacial fracture site in helmeted group was the mid-face (40.9%) and the upper-middle-lower face (26.9%) in unhelmeted group. There was no statistical significant difference between neuron-specific enolase serum levels in helmeted group (11.52 mg/ml) compared to unhelmeted group (14.49 ng/ml) ( p > 0.05). Half-coverage helmets provided motorcyclists with only limited protection in the head and facial areas. Unhelmeted motorcycle riders sustained comparable injuries compared to half-coverage helmet users.